Pengaruh Kualitas Pelayanan Kantor Pengelola Ibadah Haji Pekanbaru Terhadap Kepuasan Jamaah - Chodijah Aliya; Rifqa Zahara Putri; Aminah Aminah; Muhammad Afrizal; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to examine the influence of service quality provided by the Hajj Management Office in Pekanbaru on the satisfaction level of pilgrims. Service quality is a crucial factor in ensuring a satisfying Hajj experience, considering the complexity of the processes and services received by the pilgrims. Utilizing a quantitative approach, the research involved 100 respondents who are Hajj pilgrims from Pekanbaru. Data analysis was conducted through processing questionnaires that measured various dimensions of service quality, such as reliability, responsiveness, and empathy. The results indicate a significant positive relationship between service quality and pilgrim satisfaction. The dimensions of reliability and responsiveness had the most substantial impact on satisfaction, showing that pilgrims highly value timeliness and quick responses from the management office. The findings of this study are expected to provide insights for Hajj management in enhancing the quality of services offered. By paying attention to the aspects contributing to pilgrim satisfaction, it is hoped that the Hajj experience can be improved, leading to higher levels of satisfaction and greater value for the pilgrims’ spiritual journey.